Modification of Phu Yen diatomite and its application to Cr(VI) removal in aqueous medium - Tran, Vinh Thien (Hue University Journal of Science: Natural Science, 2023)
In this study, we successfully prepared a carboxyl-rich carbon nanomaterial from Phu Yen natural diatomite and used it as an effective adsorbent to remove Cr(VI) in aqueous media. The obtained nanomaterial was characterized by means of XRD, SEM, EDS, and FT-IR. The adsorption characteristics of Cr(VI) were investigated. pH has a significant influence on the adsorption process, and pH = 1 is optimal for Cr(VI) adsorption at ambient temperature. Three types of materials were prepared, including natural diatomite (DE), modified diatomite with carbon nanomaterial (DE/S), and modified diatomite with carboxyl-rich carbon nanomaterial (DE/C-S), and DE/C-S exhibits the highest adsorption capacity under the optimal conditions. The pseudo-second-order kinetic model and the Langmuir isotherm well describe the adsorption process of Cr(VI) onto DE/C-S with the maximum adsorption capacity of 58.82 mg·g–1, which is significantly higher compared with that of the natural diatomite (2.29 mg·g–1). Carboxyl-rich carbon-modified diatomite nanomaterials have great potential for use in removing Cr(VI) from wastewater.